Online Shop Business Owners’ Perception Toward Zakat in Langsa City - Asnita, Dessy; Agustinar; Adlin Wan Draman, Wan Mohd Ashraf (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2024)
In the perspective of Islamic law, ideally, every income that has reached the threshold should be subject to a certain amount of zakat. In reality, many online entrepreneurs in Kota Langsa are indifferent to this matter, causing academic concern behind the lack of awareness in paying zakat. This article falls under field research with a qualitative approach. The methodology used is descriptive analysis study. Primary data sources include in-depth interviews with online business operators in Kota Langsa. Secondary data sources comprise scholarly articles published within the last five years. The research concludes that the lack of awareness stems from confusion among the public regarding the amount and procedures of zakat in online trade that must be fulfilled. Therefore, governmental socialization efforts are needed to stimulate public interest in its distribution.